The Performance of the Global Sharia Equity Mutual Funds in Indonesia - TJIPTONINGSIH, UMI KAWIRYANI (2017)
This study examines the risk and returns characteristics of global sharia equity mutual funds in Indonesia. The Indonesian financial regulators released the permission to the Asset Management Companies to launch the global sharia equity funds in February 2016. This study has an objective to support Indonesian government by evaluating the performance of the Indonesian global sharia equity fund in the short-term period. To examine the fund performance, this paper is using the Jensen measure that calculated by the single index model. In additions, the benchmarks are included FTSE Sharia Asia Pacific ex Japan Index, Dow Jones Islamic Market World Index, and MSCI AC Asia Islamic ex Japan Index.